Arthroscopy-aided fixation for metacarpophalangeal joint collateral ligament injury accompanied by osteochondral avulsion injury: Our results and surgical technique (Annals of Medical Research, 2021)
None
Keywords: Stener Lesion; Fracture; Finger; Small Joints; Arthroscopic Fixation.br /